Socialization of the Spiritual Reinforcement Model to Improve Community Learning Activity Centers - Yapandi Yapandi (Universitas Tanjungpura, 2018)
This article argues that building a Community Learning Activity Center through a spiritual model can be developed in West Kalimantan for the strengthening of spiritual values. By exposing and simultaneously evaluating the concept of the current Community Learning Activity Center coaching model through Talcott Parsons functionalism to consider how individuals and communities integrate into a social system, and the concept of spiritual model and spiritual intelligence ala Danah Zohar as a form of value- spiritual values and higher goals in the lives of studying citizens, the model of empowerment through the development of spiritual models needs to be placed in a sociological, social and pedagogical setting for access to educational resources and the political system. Issues and issues of Community Learning Activity Center are never separated from human resources and local identity (identity politics), and individual and group characters. Voluntaristic displacements accept norms and social values as such, humans are actively involved in social exchanges. Likewise, one-dimensional changes, individual identities are liquid and multidimensional.